JOINT CONFERENCE – ACOUSTICS 2018 - JOINT CONFERENCE – ACOUSTICS 2018, Chronicle (Archives of Acoustics, 2018)
The paper contains the abstracts of papers presented during JOINT CONFERENCE – ACOUSTICS 2018:65th Open Seminar on Acoustics35th Symposium on HydroacousticsPolish-German Structured Conference on AcousticsUstka, Poland, September 11 – 14, 2018